WORK ENGAGEMENT IN SMES: DOES WORK SPIRITUALITY PLAY A ROLE AS A MEDIATING VARIABLE? - Parmin Parmin (Universitas Islam Lamongan, 2023)
This study aims to determine the effect of job crafting and social skills on work engagement with work spirituality as an intervening variable for MSME employees in Kebumen Regency. The population in this study were all MSME actors in Kebumen Regency. The sampling technique was based on the slovin formula and the results obtained were 71 employees. Data collection techniques by distributing questionnaires. The analysis used is validity test, reliability test, classic assumption test, hypothesis test, Sobel test, and path analysis. The data processing tool used is SPSS for Windows version 25.0. The results of this study indicate that social skills and job crafting have a positive effect on work spirituality, social skills have a positive effect on work engagement. However, the results of this study could not prove the effect of job crafting on work spirituality, and did not find a role for work spirituality as a mediation.